Advancing the Science of Cancer in Latinos Building Collaboration for Action - Ramirez, Amelie G.; Trapido, Edward J. (Springer Nature, 2023)
This open access book is a collection of articles based on presentations from the 2020 Advancing the Science of Cancer in Latinos conference that gives an overview of conference outcomes. The vision of the conference has been to unite researchers, scientists, physicians and other healthcare professionals, patient advocates, and students from across the world to discuss research advancements, identify gaps, and develop actionable goals to translate basic research findings into clinical best practices, effective community interventions, and professional training programs to decrease cancer risks and eliminate cancer disparities for Latinos. This conference comes at an especially important time when Latinos - the largest and youngest minority group in the U.S. - are expected to face a 142% rise in cancer cases in the coming years. Disparities continue to impact this population in critical areas: access to preventive and clinical care, changeable risk behaviors, quality of life, and mortality. Each chapter summarizes the presentation and includes current knowledge in the specific topic areas, identified gaps, and opportunities for future research. Topics explored include: Applying an Exposome-Wide (ExWAS) Approach to Latino Cancer Disparities Supportive Care Needs and Coping Strategies Used by Latino Men Cancer Survivors Optimizing Engagement of the Latino Community in Cancer Research Latino Population Growth and the Changing Demography of Cancer Implementation Science to Enhance the Value of Cancer Research in Latinos A Strength-Based Approach to Cancer Prevention in Latinxs Overcoming Clinical Research Disparities by Advancing Inclusive Research Advancing the Science of Cancer in Latinos: Building Collaboration for Action will appeal to a wide readership due to its comprehensive coverage of topics ranging from basic science and community prevention research to clinical practice to policy. The book is an essential resource for physicians and other medical professionals, researchers, scientists, academicians, patient advocates, and students. It also will appeal to policy-makers, NCI-designated cancer centers, academic centers, state health departments, and community organizations.